Tree regeneration in abandoned pastures in the Manaus region in relation to the distance from continuous forest - Puerta, Rogério (Scientia Forestalis/Forest Sciences, 2002)
Five 200 × 250 m plots of abandoned pasture, dominated by Brachiaria humidicola, which was formed 18 years ago (in 1981) and burned by the last time three years ago, were marked. Five distance intervals from forest edge were compared: 0 - 50 m, 50 - 100 m, 100 - 150 m, 150 - 200 m, 200 - 250 m, Density, frequency and diversity of tree species were studied with a separated survey of spread and grouped regeneration. The study was carried out at the Estelo Farm, which is part of the INPA/Smithsonian Institute Reserves, 80 km North of Manaus (central Amazonia). Sixty-five tree species from 54 genera and 27 botanic families were found in surveyed area of 6,75 hectares. The families with highest tree species diversity were Cecropiaceae (six species from three genera) and Flacourtiaceae (five species from four genera). The more abundant tree species were Vismia japurensis, V. cayennensis (Clusiaceae), and Goupia glabra (Celastraceae). However, regarding the frequency in the study plots, the species V. gulanensis ranked third instead of G. glabra. There were no significant differences for tree individuals number on distance intervals; however there was a trend for decreasing from forest edge. There were no significant differences for tree species number on distance intervals. Nevertheless, "regeneration islands" area and total number had both a significant decrease with increasing distances from the forest edge. A total area of 434 m2 of "regeneration islands" was measured at the 0-50 m interval, against 73 m2 at the 200-250 m interval; and a total of ten "regeneration islands" were found at 0-50 m against three at 200-250 m. There was a trend for decreasing tree density at "regeneration islands" with increased distance from forest edge: from 36 individuals/100 m2 at 0-50 m to 26 individuals/100 m2 at 200-250 m. Therefore, the distance to the forest edge was especially important for the "regeneration islands", where a clear decrease of tree species density and diversity was found.
Regeneração arbórea em pastagens abandonadas na região de Manaus em função da distância da floresta contínua
Keywords: Biodiversity; Degradation; Frequencies; Abandoned Pastures; Forestry; Biodiversity; Degradation; Forestry; Frequencies